การพัฒนาชุดเครื่องมือมาตรฐานระดับชาติสำหรับประเมินคุณธรรม จริยธรรม ของผู้เรียนทุกช่วงชั้น - ลังกา, วิไลลักษณ์; เจริญสุข, อรอุมา; มีชาญ, สุรชัย; ตั้งประภา, ทวิกา; ตุลย์เมธาการ, มนตา; สุวทันพรกูล, อิทธิพัทธ์; ศกุนตนาค, พนิดา (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2019)
บทคัดย่อ งานวิจัยนี้ มีวัตถุประสงค์เพื่อสร้างและตรวจสอบคุณภาพของชุดเครื่องมือมาตรฐานระดับชาติสำหรับประเมินคุณธรรม จริยธรรมของผู้เรียนในระดับชั้นประถมศึกษา มัธยมศึกษา อาชีวศึกษา และอุดมศึกษา รวมทั้งสร้างเกณฑ์ปกติของชุดเครื่องมือ และศึกษาระดับคุณธรรม จริยธรรมของผู้เรียนในทุกช่วงชั้น กลุ่มเป้าหมาย ประกอบด้วย 1) ผู้ทรงคุณวุฒิในการประชุมกลั่นกรองเครื่องมือและการวิพากษ์ จำนวน 20 คน 2) ผู้เชี่ยวชาญในการตรวจสอบความเที่ยงตรงตามเนื้อหา จำนวน 5 คน 3) กลุ่มเป้าหมายในการทดลองใช้เครื่องมือ จำนวน 600 คน 4) ตัวอย่างที่ใช้ในการสร้างเกณฑ์ปกติของเครื่องมือมาตรฐาน จำนวน 7,200 คน และ 5) ตัวอย่างในการศึกษาระดับคุณธรรม จริยธรรม จำนวน 61,200 คน ได้มาโดยการสุ่มตัวอย่างแบบหลายขั้นตอน เครื่องมือที่ใช้ในการวิจัยจำนวน 6 ฉบับ ลักษณะของเครื่องมือเป็นข้อคำถามเชิงสถานการณ์ และตัวเลือกสร้างตามแนวคิดทฤษฎีพัฒนาการทางจริยธรรมของโคลเบอร์ก ผลการวิจัย พบว่า 1) ชุดเครื่องมือสำหรับประเมินคุณธรรม จริยธรรมของผู้เรียน มี 6 ด้าน คือ ด้านความมีระเบียบวินัย ด้านความรับผิดชอบ ด้านความซื่อสัตย์สุจริต ด้านความเสียสละ ด้านความอดทนอดกลั้น และด้านความพอเพียง 2) ผลการตรวจสอบคุณภาพของชุดเครื่องมือ มีความเที่ยงตรงเชิงเนื้อหา (ค่า IOC มากกว่า 0.50 ทุกข้อ) อำนาจจำแนกอยู่ระหว่าง 0.20-0.72 ความเชื่อมั่นอยู่ระหว่าง 0.862-0.921 และความเที่ยงตรงเชิงโครงสร้าง พบว่า โมเดลการวัดคุณธรรม จริยธรรมของผู้เรียนทุกช่วงชั้น มีความสอดคล้องกับข้อมูลเชิงประจักษ์ มีค่าน้ำหนักองค์ประกอบมาตรฐานอยู่ระหว่าง 0.41-0.83 อย่างมีนัยสำคัญทางสถิติที่ระดับ .01 3) เกณฑ์ปกติในการแปลความหมายชุดเครื่องมือ โดยเทียบจากคะแนนดิบแปลงเป็นคะแนนอันดับเปอร์เซ็นไทล์ และคะแนนทีปกติ โดยผู้เรียนที่ได้คะแนนอันดับเปอร์เซ็นไทล์ที่ 50 หรือ T50 คือ ผู้เรียนที่ได้คะแนนเท่ากับค่าเฉลี่ยของกลุ่ม 4)ผลการศึกษาระดับคุณธรรม จริยธรรมของผู้เรียน พบว่า ค่าเฉลี่ยคุณธรรม จริยธรรมของผู้เรียน จำแนกตามภูมิภาค มีค่าเฉลี่ยแตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 คำสำคัญ : การประเมินคุณธรรม จริยธรรม, แบบวัดสถานการณ์, เครื่องมือมาตรฐานระดับชาติ ABSTRACT The objectives of the development of a national standard toolkit for moral evaluation of students at all ages studying at academic institutions of the Ministry of Education are to 1) create and develop a national standard toolkit for students moral evaluation, 2) find quality and norm of the national standard toolkit and 3) study moral level of students. Target groups for creating and developing the toolkit include 20 experts meeting for tool screening and criticizing. Goals of finding quality and norm of the toolkit comprise 1) 5 experts of validity assessment, 2) Experimental toolkit users for discrimination and reliability assessment students from 6 educational levels, students are comprised of 600 students 3) target groups for the toolkit’s norm development include 7,200 students and the target groups for students moral evaluation comprise 61,200 student. Research tools are comprised of 6 sets of the moral evaluation toolkits and 6 sets of civic character evaluation toolkits. These tools include situational questions and options created by following the theoretical concept of Kohlberg’s Moral Development. The finding of this research found that 1) The moral evaluation toolkit is comprised of 6 aspects including honesty, sacrifice, tolerance, responsibility, modesty, and discipline. 2) Results of the study on quality and norm of the national standard toolkit: Content validity: the analysis of the Item-Objective Congruence Index (IOC) for all questions were higher than 0.50. Discrimination: between 0.20-0.72 Reliability assessment: between 0.862 and 0.921. Construct validity assessment: found that the moral evaluation model for students at all level conforms to the empirical data. the aspect’s standard weight between 0.41-0.83 and all aspects are statically significant at 0.01 level. 3) Norm: The researcher has created norm for interpretation of the national standard toolkit for moral evaluation for students at all levels by comparing with raw score and transforming to percentile score and normal scores. Students with percentile level 50, or T50, are those students whose scores are equal to the group’s average score. 4) Results of comparing the average moral scores of students classified by regions found that students all level classified by regions have average moral score different at statistical significance level of .05 Keywords: Moral Evaluation, Situation Form, National Standard Toolkit